Early career GPs, mental health training and clinical complexity: a cross-sectional analysis. Issue 2 (4th March 2019) - Stone, Louise; Tapley, Amanda; Presser, Jennifer; Holliday, Elizabeth; Ball, Jean; Van Driel, Mieke; Davey, Andrew; Spike, Neil; Fitzgerald, Kristen; Mulquiney, Katie; Morgan, Simon; Magin, Parker
ABSTRACT: Patients with mental health conditions commonly present in General Practice. Mental health curricula are broad. We do not know that trainees are exposed to the learning they require. This study aimed to establish the prevalence, characteristics and associations of GP trainees' management of mental health problems. This paper presents a cross-sectional analysis of the Registrar Clinical Encounters in Training (ReCEnT) study, an ongoing multisite cohort study of Australian GP trainees (registrars) documenting their clinical experiences over 60 consecutive consultations. Univariate and multivariable logistic regression analyses were conducted with outcome of the problem/diagnosis being a mental health condition. 1659 trainees provided data on 218, 325 consultations and 340, 453 problems/diagnoses. Mental health conditions were associated with patients being male, of Aboriginal or Torres Strait Islander or English-speaking background. Trainee characteristics were being more senior and having trained in Australia. Practice characteristics included being in low socioeconomic areas. Trainees sought less help for mental health concerns than they did for other problems. While early-career GPs see a broad range of mental health conditions, they may benefit from training to manage patients from cross-cultural contexts. They may also need support to generate appropriate learning goals and seek assistance if they are to continue to deepen competence.